A Review on The Development of Panel and Membrane Sound Absorbers - Hamdan, Nur Izzah; Zainulabidin, Muhd Hafeez; Ismail, Al Emran; Mohd Kassim, Angzzas Sari (International Journal of Integrated Engineering, 2021)
Noise pollution has become one of the most serious environmental problems, especially in developing countries. Noise pollution caused discomfort, dizziness, and continuous exposure to an excessive amount of it affects human health both physically and psychologically. The utilization of sound absorption material has become an effective solution in reducing or controlling this noise pollution problem. Panel and membrane material getting more attention because of its effectiveness in absorbing low-frequency sounds, more hygienic and safer to human health compared to the porous material. Therefore, the panel and membrane absorbers have been developed rapidly in various fields and also have evolved to become more designable, advanced, and efficient in absorbing sound. However, combinations of membrane or panel absorber with porous materials are still advantageous in term of sound absorption performance and even worth considering. This paper aims to provide an information and literature study on panel and membrane absorbers evolution in the past decades in terms of improving the sound quality. This paper also covers the introduction of panel and membrane sound absorption system, variations of panel and membrane absorber concepts, and factors affecting the absorption performance of the materials. From the review, material properties such as mass density, air cavity, thickness, and perforation found to influence sound absorption performances. By looking at the intensity of research and progress of panel or membrane absorber, it is predicted that there will be more development and improvement of panel and membrane absorbers. Therefore, it is essential to review the progress and development of the panel and membrane absorbers to give a better understanding of their absorption characteristics and to seek new research opportunities in the future.